2005
DOI: 10.1136/jcp.2004.023572
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 expression is a novel prognostic factor in patients with invasive ductal carcinoma of the pancreas

Abstract: Background: Many patients with invasive ductal carcinoma of the pancreas (IDC) have a poor outcome. MUC4 expression has been implicated as a marker for diagnosis and progression of IDC, but there are no studies of the relation between MUC4 expression and patient prognosis in IDC. Aims: To investigate the prognostic significance of MUC4 expression in IDC. Methods: The expression profiles of MUC4, ErbB2, p27, and MUC1 were investigated in IDC tissues from 135 patients by means of immunohistochemistry. Results: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
134
4
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 50 publications
18
134
4
3
Order By: Relevance
“…The evidence that Muc4 potentiates HER2 signaling has led to the hypothesis that it may promote HER2 tumorigenic signaling even in tumors that do not overexpress HER2. Consistent with this hypothesis, increased expression of Muc4 is associated with worse prognosis in several types of cancer (Shibahara et al, 2004;Saitou et al, 2005;Tamada et al, 2006;Tsutsumida et al, 2006). Further analysis of this hypothesis awaits models that more definitively demonstrate the role of Muc4 in promoting tumorigenic HER2 function.…”
Section: Cell Cycle Deregulationmentioning
confidence: 52%
“…The evidence that Muc4 potentiates HER2 signaling has led to the hypothesis that it may promote HER2 tumorigenic signaling even in tumors that do not overexpress HER2. Consistent with this hypothesis, increased expression of Muc4 is associated with worse prognosis in several types of cancer (Shibahara et al, 2004;Saitou et al, 2005;Tamada et al, 2006;Tsutsumida et al, 2006). Further analysis of this hypothesis awaits models that more definitively demonstrate the role of Muc4 in promoting tumorigenic HER2 function.…”
Section: Cell Cycle Deregulationmentioning
confidence: 52%
“…In addition, prostate cancer has exhibited downregulation of MUC4 expression in prostate carcinomas as compared with that in the normal/benign prostate regions. In contrast to the aforementioned studies, high MUC4 expression correlates with a short disease-free interval and a poor survival rate of small-sized lung adenocarcinomas, cholangiocarcinomas, epithelial ovarian carcinomas, pancreatic cancers and colorectal adenocarcinoma (12)(13)(14)(15)(16)25,26). MUC4 overexpression in gastric cancer tissues compared with normal adjacent tissues has been previously reported (27).…”
Section: Discussionmentioning
confidence: 48%
“…The overexpression of MUC4 has been discovered in a number of human neoplasms (10)(11)(12). It has been shown that MUC4 expression is related to aggressive tumor behavior or a poor outcome in intrahepatic cholangiocarcinoma, invasive ductal carcinoma of the pancreas, extrahepatic bile duct carcinoma, and lung adenocarcinoma (13)(14)(15)(16)(17). On the other hand, loss of MUC4 expression is related to poor survival in mucoepidermoid carcinoma of the salivary gland, squamous cell carcinoma of the upper aerodigestive system, and adenocarcinoma of lung (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…10,[12][13][14] An over expression of MUC4 is observed in pancreatic, lung, breast, colon, and ovarian malignancies, suggesting its pathologic significance and the association of MUC4 with the poor prognosis of the pancreas, lung, and bile duct cancer patients has also been reported. 9,11,[15][16][17][18][19] In the present study, we have determined the expression of MUC 4 in prostatic adenocarcinoma and its correlation with clinicopathological data.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A total of 21 human mucin genes (MUC1-MUC4) have been identified and subclassified into three groups: transmembrane, gel forming or secreted and soluble mucins. 4,[8][9][10] Transmembrane mucins contribute to epithelial cell-cell interactions and secreted mucins form a physical barrier to provide protection for epithelial cells. 4,8 In addition, mucin control many cellular processes, including growth, differentiation, transformation, adhesion, invasion, and immune surveillance.…”
Section: Introductionmentioning
confidence: 99%